PENGEMBANGAN INSTRUMEN TES PEMAHAMAN KONSEP TRANSFORMASI GEOMETRI BERBASIS ETNOMATEMATIKA - Rensiana, Melza; Dwirahayu, Gelar; Putri, Finola Marta (Math Educa Journal, 2024)
This study aims to develop an instrument test geometric transformation using context of Banten culture. The method is RD with model Wilson, which is consist of 3 stages: design testing, trial testing, and testing assembly. The feasibility of the instrument was measured based on content validity by two lecture of mathematics education and five mathematics teacher at senior high school and empirical validity, reliability, discriminating power and level of difficulty. The results showed that the instrument test shows eligibility criteria based on content validity and empirical validity, the high reliability category, the difficulty level was divided into easy questions 40%), moderate questions (48%), and difficult questions (12%), and different power questions met the criteria of good (40%) and sufficient (60%). Thus, researchers can conclude that instrument test using context Banten culture can use to measure understanding of the concept of geometric transformation at high school.